APPLICATION OF NEW CONSTRUCTIONS OF SLIP BEARING WITH MOBILE SPRING INSERT FOR NAVIES OF TRANSPORT EQUIPMENT [Text] - Kushaliyev, D.K.; Baltayev, T. A.; Ermanova, B. A. (Science and education №3, 2018)
The design of a sliding bearing for reciprocating rotational motion with a movable spring liner is presented, which can be used in various units of transport equipment and process equipment. The working surfaces of the bearing operate in a selective transfer mode, thereby providing an effect of non-uniformity. The mode and uniformity of wear is achieved with the return-rotational movement of the shaft or outer ring due to the twisting and unwinding of the spring liner, braking occurs respectively on the inner or outer surface of the spring insert («ratchet effect») only in one direction, depending on the direction of winding the spring. In the process of work, the contact line on the working surfaces changes, which also leads to a decrease in their wear and tear. The process of manufacturing the bearing parts simplifies and simplifies the assembly process itself.Представлена конструкция подшипника скольжения для возвратно-вращательного движения с подвижным пружинным вкладышем, который может быть использован в различных узлах транспортной техники и технологического оборудования. Рабочие поверхности подшипника работают в режиме избирательного переноса, за счет чего обеспечивается эффект безызностности.
Keywords: рк; научный журнал; периодическое издание; отечественное издание; техника; подшипник скольжения; bearing; spring; ratchet; insert